발모광 뇌영상 연구의 과거, 현재와 미래 - 이지아(Jiah Lee); 김철권(Chul Kwon Kim); 김윤정(Yoon Jung Kim); 반건호(Geon Ho Bahn) (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2009)
Trichotillomania (TTM) is a disorder characterized by repetitive hair pulling, frequently from the scalp and/or eyebrows, leading to noticeable hair loss and functional impairment. TTM remains a poorly understood and inadequately treated disorder despite increased recognition of its prevalence. We review available neuroimaging studies conducted in patients with TTM, covering structural and functional neuroimaging in turn. Data from patients' structural and functional neuroimaging results enabled us to identify the neural circuitry involved in the manifestation of hair pulling. Finally, we highlighted the future importance of neuroimaging studies in children and adolescents with TTM.